Contraception and preconception counseling in special populations. (September 2011) - Zilberman, Dimitry; Sridhar, Aparna; Roche, Natalie; Gittens-Williams, Lisa
While all women of reproductive age should be counseled regarding their contraception options, appropriate contraceptive management is critical for patients with underlying medical conditions where pregnancy may engender certain maternal and/or fetal risks. Whereas management of conditions such as mental illness, obesity, autoimmune disease, solid organ transplant and gynecological malignancies is complex and often requires expert consultation, effective contraceptive management in these groups can reduce risks and improve outcomes. It is critical, therefore, that clinicians who are caring for such patients understand contraceptive options in such women. In this article, preconception counseling, contraception options and obstetrical risks that these conditions may impose upon pregnancy are reviewed.